SOFTWARE RISK TAXONOMY CREATION BASED ON THE COMPREHENSIVE DEVELOPMENT PROCESSES - M. Lyashkevych; I. Rohatskyi; V. Lyashkevych; Roman Shuvar (Електроніка та інформаційні технології, 2024)
Software risks are always a crucially important topic for research because the software development process is quite expensive. The competition is high enough to ignore it. Although the "golden" era for startup projects is slowly ending, the latest achievements in generative AI show that now is the time to "take risks" and capture the software market using this technology. Therefore, it is necessary to analyse already known risks and identify new risks associated with business models and market conditions with generative AI capacity.